Acne in pregnancy: A prospective multicenter, cross-sectional study of 295 patients in Turkey - Kutlu, Ömer; Karadağ, Ayşe Serap; Ünal, Emine; Kelekçi, Kıymet Handan; Yalçınkaya İyidal, Ayşegül; Topaloğlu Demir, Filiz; Aksoy, Berna; Çölgeçen, Emine; Tosun, Mustafa; Emre, Selma; Tatlıparmak, Aslı; Demirseren, Duriye Deniz; et al. (Wiley, 2020)
Background There are only a few studies on acne in pregnancy. This study was aimed to investigate the demographic, clinical, and familial characteristics of acne in pregnancy, triggering factors including endocrine diseases, and association of these findings with acne in different trimesters of pregnancy. Methods Pregnant women aged 18 years and older with acne at any stage of pregnancy were consecutively interviewed at the participating centers during the study period from 2016 to 2019. Acne severity was evaluated using the Comprehensive Acne Severity Scale. Results A total of 295 pregnant women with acne were included, with 167 (56.6%) patients showing mild, 87 (29.5%) moderate, six (12.2%) severe, and five (1.7%) very severe acne. Truncal acne was significantly higher in the third trimester than in the other stages (P < 0.001). Onset of acne before pregnancy, prepubertal, pubertal or adult onset, or acne history in previous pregnancies did not influence acne severity in pregnancy. Women with irregular menstruation before pregnancy, polycystic ovary syndrome, hirsutism, and higher body weight index tended to show severe acne in pregnancy. Conclusions Severe acne during pregnancy is generally uncommon, while severity of facial acne, truncal acne, and hirsutism is higher in the third trimester than in other trimesters. Acne in pregnancy shares many characteristics with female adult acne. Substantial changes in different kinds of hormones play a more complex role in acne during pregnancy, but the pathogenesis remains to be determined.
Keywords: Acne; Cross-Sectional Study; Turkey; Demographic